IL-13-Mediated Gender Difference in Susceptibility to Autoimmune Encephalomyelitis - Sinha, Sushmita (2008)
Females tend to have stronger Th1-mediated immune responses and are more prone to develop autoimmune diseases, including multiple sclerosis. Macrophages are major effector cells capable of mediating or modulating immune responses in experimental autoimmune encephalomyelitis (EAE). IL-13 and estrogen have opposing roles on macrophages (the former enhancing and the latter inhibiting) in terms of MHC class II (MHC II) up-regulation and, thus, these factors might influence susceptibility to EAE differently in females vs males. In accordance with this hypothesis, females lacking IL-13 displayed lower incidence and milder EAE disease severity than males after immunization with myelin oligodendrocyte glycoprotein (MOG)-35–55 peptide/CFA/pertussis toxin. Female IL-13 knockout (KO) mice with EAE consistently had reduced infiltration of CD11b(+) macrophages in the CNS along with significantly reduced expression of MHC II on these cells. Impaired MHC II expression was further corroborated upon LPS stimulation of female but not male bone marrow-derived CD11b(+) macrophages from IL-13KO mice, with restored expression after IL-13 pretreatment of female but not male macrophages. APCs from IL-13KO females induced less proliferation by MOG-35–55-reactive T cells, and splenocytes from MOG peptide-immunized females had lower expression of IL-12, IFN-γ, MIP-2, and IFN-γ-inducible protein 10 than males. In contrast, these splenocytes had higher expression of anti-inflammatory factors, IL-10, TGF-β1, and FoxP3, a cytokine pattern typical of regulatory type II monocytes. These data suggest that the difference in EAE susceptibility in females is strongly influenced by gender-specific proinflammatory effects of IL-13, mediated in part through up-regulation of Th1-inducing cytokines and MHC II on CD11b(+) macrophages.